Assessing human capacity in monitoring and evaluation systems of health centres in Mpumalanga province - Mashego, Sydwell Lethabo (My University, 2017)
There is a need to improve the functioning of health centres in Mpumalanga province. In order to improve public service delivery and the health of Mpumalanga citizens, it is important to have a well-functioning M&E system. The rationale for the research is to assess human capacity in Monitoring and Evaluation (M&E) of Health Centres in Mpumalanga Province. The research will unpack the department programmes and objectives. The research will assess human capacity gaps in the implementation of an M&E system. The study will also assess whether M&E unit has enough budget to undertake M&E activities. Stakeholder relationship will also be assessed between MDoH M&E unit and other departments. If there is no human capacity gaps an assessment will be done on the success factors. The findings of the study are important in determining the factors that prevents health centres from achieving their goals and objectives. The recommendations for the study can be used by MDoH M&E unit and other organisations in strengthening their policies for effective functioning of their health centres. Using qualitative research strategy and unstructured interviews, participants were interviewed and the results revealed that there is a lack of human capacity and financial resources specifically referring to budget to undertake M&E activities. The study discovered that there are no plans in place to solve capacity gaps in the unit. In addition the study discovered that there are is no capacity building initiatives to capacitate and strengthen the skills development of employees. Lack of stakeholder relationship between MDoH M&E unit and other departments formed part of the findings. The overall findings of the research are attributed by lack of prioritisation by managers who do not view M&E unit as a priority of the MDoH. In addition the study found that MDoH M&E unit is also failing to apply New Public Management (NPM) in the execution of their M&E functions. The recommendations of the study include strengthening M&E unit, through budget allocation. The budget will help to address existing capacity gaps and capacity building initiatives. Stakeholder relationship is also important in improving the performance of MDoH M&E unit.
Research Report presented in partial fulfillment of the degree of Master of Management (in the field of Public and Development Management) in the Faculty of Commerce, Law, and Management, at the University of the Witwatersrand, Johannesburg. March 2017
Keywords: Performance standards--South Africa--Evaluation; Civil service reform--South Africa